PROVIDING FOREIGN LANGUAGE PROFESSIONAL ORIENTATION OF THE PROFESSIONAL TRAINING PROCESS OF FUTURE LAWYERS - Demchenko, D.I. (Pedagogy of Higher and Secondary Education, 2010)
The article is devoted description of pedagogical condition of providing of efficiency of forming of foreign professional competence of future representatives of legal profession in the process of their professional preparation in higher legal educational establishment.